Optimalisasi Manajemen Infrastruktur Berbasis Risiko dalam Pengurangan Bencana Banjir di Kawasan Perkotaan - Buyung Mantap; Yoka Mahendra; Hendret Susanto (Journal of Science, Technology, and Innovation, 2026)
Urban flooding represents a systemic risk emerging from the interaction between hydrological hazards, spatial transformation, and infrastructure vulnerability, demanding a management paradigm that transcends conventional engineering responses. This study develops a non-empirical conceptual framework for optimizing risk-based infrastructure management to strengthen urban flood resilience. The framework integrates infrastructure asset lifecycle management, disaster risk theory, and urban governance into a multilayer analytical model that explains causal relations among planning, implementation, maintenance, and adaptive capacity. A systematic literature synthesis and thematic-critical analysis were employed to construct stable conceptual propositions and evaluate internal coherence across disciplines. Findings indicate that preventive planning, adaptive asset management, institutional coordination, and participatory monitoring operate as interdependent mechanisms that reduce system fragility and enhance operational learning. The proposed model provides an analytical structure for evaluating infrastructure effectiveness without dependence on a single empirical context while preserving methodological rigor. This study contributes theoretically by linking risk governance with lifecycle infrastructure management and methodologically by offering a replicable conceptual synthesis for resilient urban systems.